Biological maturity and performance in youth alpine skiing: An analysis of motor skills and sport specific skills - Pelizzatti, G.; Modena, R.; Bortolan, L.; Pellegrini, B.; Zoppirolli, C. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: Alpine skiing is a complex sport that requires advanced agility, dexterity, and significant muscular engagement, primarily relying on anaerobic metabolism [1]. However, when considering young athletes, it is crucial to monitor and account for additional variables such us physical and biological growth, as well as gender differences, since boys and girls experience different rates of physical and performance development [2; 3]. The present study examined anthropometry, biological maturation, physical performance capacity and training habits in young alpine skiers, in relation to their actual alpine skiing performance capacity.